A gím-és dámszarvas testtömegének és egyes trófeaparaméterek változása az elmúlt 30 évben - Czakó Attila (2017)
I made my diploma at the sylviculture of Lábod, what belongs to SEFAG forestry and wood industry Zrt. We ccan locate at this territory the best red deer and fallow deer population in Hungary, what is a highlighted area about the wiew of preservation of gene sources. First of all I examined the different considerations what effects the size of trophies. I also studied the connection of body weight, taking notice the studies and sightings of different specialist in hungarian and international area too. I tried to draw the most inference during my conclusions, and formulate an accurate result what is strengthened by evidences. In the case of red deer stag is predicabile, that the climatic factors what were used by me, for the size of trophies the most important things are the average precipitation of March and the duration of sunshine in April. In the case of fallow deer I did not find connection between the size of trophies and the different meteorological circumstances. The body weight and the trophy weight datas did not show any connection.